Impact of radicalism and terrorism through social media among youth in the Film The Lone Wolf Next Door - Muchammad Zaenal Al Ansory; Anggar Erdhina Adi (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
This research delves into the detrimental impacts of social media utilization among young individuals as a conduit for radicalism and terrorism propagation. Focusing on